Comparative evaluation of the composition of vegetable essential and fixed oils obtained by supercritical extraction and conventional techniques: a chemometric approach. (25th May 2021) - Piras, Alessandra; Piras, Cristina; Porcedda, Silvia; Rosa, Antonella
Summary: We compared by a chemometric approach the composition of essential (EO) and fixed (FO) oils previously obtained from several vegetable matrices by supercritical CO2 extraction (CO2 ‐SFE) and conventional techniques ( n ‐hexane in a Soxhlet apparatus and hydrodistillation). A multivariate approach, by determining the principal components analysis (PCA) applied to data of FO fatty acids and EO volatile compounds, generally indicated that the vegetable oils extracted with CO2 ‐SFE tightly clustered with those obtained by conventional methods. The graphical distances calculated in the PCA plots between the score of each SFE oil and the corresponding conventional oil revealed that the CO2 ‐SFE FO and EO profiles were quite similar to conventional oils, with the additional benefit of not having unwanted traces of solvent. SFE FO were more similar to conventional oils than SFE EO (mean values of calculated graphical distances were 0.83 and 1.46 for FO and EO, respectively). Our results strongly corroborate the role of CO2 ‐SFE as a suitable, environmentally safe and efficient method alternative to the traditional ones for the extraction of natural vegetable oils for food and pharmaceutical applications. Abstract : Chemometric comparison of fixed and essential oil composition. ​